The Effects of Ivacaftor on Bone Density and Microarchitecture in Children and Adults with Cystic Fibrosis - Putman, Melissa S; Greenblatt, Logan B; Bruce, Michael; Joseph, Taisha; Lee, Hang; Sawicki, Gregory; Uluer, Ahmet; Sicilian, Leonard; Neuringer, Isabel; Gordon, Catherine M; Bouxsein, Mary L; Finkelstein, Joel S (The journal of clinical endocrinology and metabolism, 2021)
Abstract Context Cystic fibrosis (CF) transmembrane conductance (CFTR) dysfunction may play a role in CF-related bone disease (CFBD). Ivacaftor is a CFTR potentiator effective in improving pulmonary and nutritional outcomes in patients with the G551D-CFTR mutation. The effects of ivacaftor on bone health are unknown. Objective To determine the impact of ivacaftor on bone density and microarchitecture in children and adults with CF. Design Prospective observational multiple cohort study. Setting Outpatient clinical research center within a tertiary academic medical center. Patients or Other Participants Three cohorts of age-, race-, and gender-matched subjects were enrolled: 26 subjects (15 adults and 11 children) with CF and the G551D-CFTR mutation who were planning to start or had started treatment with ivacaftor within 3 months (Ivacaftor cohort), 26 subjects with CF were not treated with ivacaftor (CF Control cohort), and 26 healthy volunteers. Interventions All treatments, including Ivacaftor, were managed by the subjects’ pulmonologists. Main Outcome Measures Bone microarchitecture by high-resolution peripheral quantitative computed tomography (HR-pQCT), areal bone mineral density (aBMD) by dual-energy X-ray absorptiometry (DXA) and bone turnover markers at baseline, 1, and 2 years. Results Cortical volume, area, and porosity at the radius and tibia increased significantly in adults in the Ivacaftor cohort. No significant differences were observed in changes in aBMD, trabecular microarchitecture, or estimated bone strength in adults or in any outcome measures in children. Conclusions Treatment with ivacaftor was associated with increases in cortical microarchitecture in adults with CF. Further studies are needed to understand the implications of these findings.